Drones, Signals, and the Techno-Colonisation of Landscape - Fox, Kathryn Ann (Curtin University, 2023)
This research project is a cross-disciplinary, creative practice-led investigation that interrogates increasing military interest in the electromagnetic spectrum (EMS). The project’s central argument is that painted visualisations of normally invisible aspects of contemporary EMS-enabled warfare can reveal useful, novel, and speculative but informed perspectives that contribute to debates about war and technology. It pays particular attention to how visualising normally invisible signals reveals an insidious techno-colonisation of our extended environment from Earth to orbiting satellites.